The Singing Style of Kamariah Noor: An Analytical Study of Singing Style in Lagu Melayu Asli - Junaidi , Syazwan bin; Saidon, Zaharul Lailiddin bin (Grenek: Jurnal Seni Musik, 2025)
The preservation and revitalization of traditional musical performance practices represent critical challenges in contemporary ethnomusicological discourse, particularly within the context of Malay musical heritage. This research proposes a comprehensive strategy for rejuvenating Lagu Melayu Asli (LMA) through systematic integration of Kamariah Noor’s (KN) distinctive singing style, which have been marginalized by current performance standardization. This research also examines the distinctive vocal characteristics and musical techniques of KN, a prominent singer in LMA. Through comprehensive discographic analysis and expert interviews, this study explores KN’s unique singing style, focusing on her singing motifs in the singing style of LMA.